Limitations of the Unified Multiple System Atrophy Rating Scale as outcome measure for clinical trials and a roadmap for improvement - Palma, Jose-Alberto (Clin Auton Res, 2021)
PURPOSE: The unified multiple system atrophy (MSA) rating scale (UMSARS) was developed almost 20 years ago as a clinical rating scale to capture multiple aspects of the disease. With its widespread use, the shortcomings of the UMSARS as a clinical outcome assessment (COA) have become increasingly apparent. We here summarize the shortcomings of the scale, confirm some of its limitations with data from the Natural History Study of the Synucleinopathies (NHSS), and suggest a framework to develop and validate an improved COA to be used in future clinical trials of disease-modifying drugs in patients with MSA. METHODS: Expert consensus assessment of the limitations of the UMSARS and recommendations for the development and validation of a novel COA for MSA. We used UMSARS data from the ongoing NHSS (ClinicalTrials.gov: NCT01799915) to showcase some of these limitations. RESULTS: The UMSARS in general, and specific items in particular, have limitations to detect change resulting in a ceiling effect. Some items have specific limitations including unclear anchoring descriptions, lack of correlation with disease severity, susceptibility to improve with symptomatic therapies (e.g., orthostatic hypotension, constipation, and bladder dysfunction), and redundancy, among others. CONCLUSIONS: Because of the limitations of the UMSARS, developing and validating an improved COA is a priority. The time is right for academic MSA clinicians together with industry, professional societies, and patient advocacy groups to develop and validate a new COA.